H2O2-replenishable and GSH-depletive ROS 'bomb' for self-enhanced chemodynamic therapy. Issue 2 (13th December 2021) - Zhao, Fan; Yao, Jiayu; Tong, Yu; Su, Dan; Xu, Qing; Ying, Yao; Li, Wangchang; Li, Juan; Zheng, Jingwu; Qiao, Liang; Cai, Wei; Mou, Xiaozhou; et al.
Abstract : CaO2 -Fe NPs are good candidates for constructing ROS 'bomb' with endogenous replenishment of H2 O2 and depletion of GSH, achieving self-enhanced chemodynamic therapy. Abstract : Chemodynamic therapy (CDT) is an emerging strategy of tumor therapy that utilizes the Fenton reagent to kill tumor cells by disproportionation of H2 O2 into hydroxyl radical (˙OH). However, insufficient endogenous H2 O2 confines the antitumor efficacy of CDT. Additionally, the overexpressed glutathione (GSH) exhibits a potent scavenging effect on cytotoxic ˙OH, which further diminishes the efficacy of CDT. Though tremendous efforts have been done, engineering CDT agents with efficient and specific H2 O2 self-supplying and GSH-depletion is promising but remains a great challenge. Herein, Fe 3+ –chelated CaO2 nanoparticles (CaO2 –Fe NPs) are constructed as ROS 'bomb'. In the tumor microenvironment, CaO2 –Fe NPs can release Fe 2+ by the reduction of GSH, and the remaining CaO2 reacts with H + to selectively generate H2 O2 . The generated H2 O2 can produce ˙OH under the catalysis of Fe 2+ through the Fenton reaction, and re-oxidation from Fe 2+ to Fe 3+ endowing a long-lasting GSH-depletion, resulting in an improved CDT. These CaO2 –Fe NPs supply H2 O2 and exhaust GSH simultaneously to achieve a self-enhanced CDT, and paves an emerging strategy to enhance the therapeutic efficacy of CDT by combining H2 O2 -replenishable and GSH-depletive together and realizing a self-enhanced Fenton reaction cycle.